NON-DISRUPTIVE GENE TARGETING - BARKER, Jenny; KAY, Mark A; CHECKETTS, Josh; BARZEL, Adi; PORTEUS, Matthew; VOIT, Richard (2021)
Compositions and methods are provided for integrating one or more genes of interest into cellular DNA without substantially disrupting the expression of the gene at the locus of integration, i.e., the target locus. These compositions and methods are useful in any in vitro or in vivo application in which it is desirable to express a gene of interest in the same spatially and temporally restricted pattern as that of a gene at a target locus while maintaining the expression of the gene at the target locus, for example, to treat disease, in the production of genetically modified organisms in agriculture, in the large scale production of proteins by cells for therapeutic, diagnostic, or research purposes, in the induction of iPS cells for therapeutic, diagnostic, or research purposes, in biological research, etc. Reagents, devices and kits thereof that find use in practicing the subject methods are also provided.